Enhancing Pillar Stability in a Deep-Cover Longwall Mine Using the LaModel Program: A Comparative Analysis - SME Annual Meeting 2025 - Morgan M. Sears (Society for Mining, Metallurgy & Exploration, 2025)
The stability of gateroad pillars is crucial in deep-cover longwall mining, especially during transitions to wider panel layouts. This study evaluates the transition from a 700-foot to a 1,000-foot panel layout with an inter-panel barrier in a deep-cover longwall mine in Southwestern Virginia to identify a configuration that enhances stability and reduces operational risks. Using the LaModel program, three pillar configurations were simulated to assess their performance based on stress distributions and pillar safety factors. These included the previously used 4-Entry Yield-Abutment-Yield layout, the current 3-Entry Yield-Abutment layout with a 220-ft inter-panel barrier, and the proposed 3-Entry Yield-Yield layout with a 320-ft inter-panel barrier. The findings of this study suggest that the proposed 3-Entry Yield-Yield pillar layout is more effective in managing stresses in deep-cover mining environments. By optimizing pillar placement and improving load management, this layout could positively impact mineworker safety and health. The study underscores the importance of advanced simulation tools in developing innovative solutions to address the challenges of modern longwall mining operations.